Smartphone Utilization and Its Impact on Student Learn-ing Motivation in Islamic Religious Education from a Self-Regulated Learning Perspective - Hasanuddin, Hasanuddin; Ahmad Sukandar (Journal of Science and Education (JSE), 2026)
The utilization of smartphones in Islamic Religious Education (PAI) learning presents both challenges and opportunities to enhance students’ learning motivation. This article aims to identify the impact of smartphone usage on the learning motivation of junior high school students from the perspective of Self-Regulated Learning (SRL) and to explore self-regulation strategies in managing this technology. The study employed a comparative case study method with a qualitative-dominant mixed-methods approach, involving two public junior high schools in Cianjur, Indonesia. Data were collected through interviews, observations, and questionnaires, then analyzed thematically and descriptively. The results show that smartphones can stimulate both extrinsic and intrinsic motivation, contingent upon students’ level of self-regulation. Smartphones function as a medium for learning access, digital proselytization (da'wah), and spiritual reflection. However, distraction remains a challenge where self-control is weak. Factors such as school environment, teachers’ roles as religious digital models, parental support, and religiosity significantly influence motivation. Self-regulated learning strategies, including goal awareness, time management, distraction control, and social-spiritual support, are essential for optimizing smartphone use. Smartphone use must be accompanied by digital literacy development that integrates academic competencies and Islamic values to be an effective and meaningful learning tool.